The semantic web : latest advances and new domains : 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31-June 4, 2015. Proceedings /: latest advances and new domains : 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31-June 4, 2015. Proceedings. (2015) - Unknown
No abstract available